ANALISA KEBIJAKAN PEMERINTAH TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI KOTA TANJUNGPINANG - Hery Haryanto; Benedicte Hartono; Carol Carol; Desi Pratama; Shirlyn Shirlyn; Winky Winky (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This article aims to analyze problems one of the cities in Indonesia namely Tanjungpinang, how many unemployed people, how to reduce and how much the impact of inflation affects the city. The research method are combined research methods qualitative and quantitative. The results obtained from the data obtained by the author. In 2022, Tanjungpinang has movement figures that reach 6,000 (six thousand) people. From the inflation data in Tanjungpinang City 2022, there is an increase.